"Surround the Workpiece": Herman Chui from Spectra‐Physics Lasers and Christian Dini from Ophir explain the new offering from MKS Instruments. Issue 4 (1st August 2019) - Unknown
Abstract: At this year's Laser World of Photonics, MKS Instruments brands Spectra‐Physics, Newport, and Ophir demonstrated their joint portfolio for laser materials processing. We asked Herman Chui and Christian Dini, what benefits customers can expect.